Analysis of the Effect of Debt Level, Market Orientation, and Financial Literacy on Microenterprise Financial Performance: The Mediating Role of Consumer Behavior - Siti Mariam; Aditya Halim Perdana Kusuma Putra; Abdul Haeba Ramli; Fika Aryani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
In the context of business and consumer behavior, this paper explores the impact of Debt Level, Market Orientation, and Financial Literacy on Consumer Behavior and Microenterprise Financial Performance. The purpose of this study is to examine the role of Debt Level, Market Orientation, and Financial Literacy in managing financial risk, shaping consumer behavior, and improving financial performance of small firms. The study utilizes a comprehensive analysis of key elements including Debt Level (Amount of Debt, Debt Interest Rate, Duration of Debt, and Debt to Asset Ratio), Market Orientation (Market Segmentation, Marketing Strategies, and Customer Satisfaction Level), and Financial Literacy (Knowledge of Interest and Interest Rates, Understanding of Investments, and Ability to Manage Budgets). The study examines the managerial and consumer implications of these factors. The findings suggest that wise debt management is crucial for maintaining positive consumer relationships and achieving good financial performance. Similarly, understanding the market, employing relevant marketing strategies, and focusing on customer satisfaction are important for shaping consumer behavior and improving financial performance. Additionally, improving financial literacy at both individual and organizational levels positively impacts consumer behavior and financial performance. This study highlights the importance of Debt Level, Market Orientation, and Financial Literacy in the business and consumer ecosystem. It emphasizes the need for awareness, education, and wise management for achieving positive consumer relations and financial success. The study provides valuable insights for firms to improve their financial performance while meeting consumer needs and encourages consumers to make wiser financial decisions.